GAMBARAN UMUM PELAYANAN PENDAFTARAN RAWAT JALAN DI RS SANTA ELISABETH BATAM KOTA - Masriani Situmorang; Rahmawati Rahmawati; Fani Farhansyah (Politeknik Negeri Jember, 2023)
Registration services are the first type of service that interacts directly with patients. The outpatient registration procedure of each hospital has a different service system that depends on the policies of each hospital. Hospitals have an outpatient registration process that is still not optimal and there are still many patients who do not understand the outpatient registration process. This study aims to find out an overview of outpatient registration services at Santa Elisabeth Hospital Batam City. This research used qualitative methods with interviews and direct observation / observation at Santa Elisabeth Hospital Batam City. From the results of the study, the outpatient registration system at Santa Elisabeth Hospital Batam City was obtained directly, and indirectly (by telephone). During the service process, there were several problems that occurred, including patients not knowing that the queue number to see a certain doctor was separated, resulting in patients who had taken the queue number on the queue machine returning to the security guard table to retrieve the new queue number, as well as an error Information System Server. The flow of outpatient services at Santa Elisabeth Hospital Batam City is in accordance with the SOP although there are still some problems at the Outpatient Registration Site (TPPRJ).